Supplementation research at Massey University - Ali, A. (Elite Training Seminar Series, 2019)
The speaker will be presenting some of the supplementation projects that are currently undertaking at Massey University including caffeine, beetroot juice, oral rehydration solutions, and pickle juice. These are multi-disciplinary studies comprising food technology, sensory science, biochemistry, nutrition, psychology and sport and exercise.